Standar Reservasi Dalam Peningkatan Penjualan Kamar Di Hotel Duta Syariah Palembang - Nyayu Ully Auliana (Student Research Journal, 2023)
Hotel Duta Syariah is a two-star hotel which has experienced a decline in room sales due to the impact of the co-19 pandemic. During a pandemic like this, to increase sales, an effective promotion strategy is needed so that room sales increase again. So, the purpose of this study is to find out how the promotion strategy carried out by Duta Syariah Hotel is to increase room sales during the Covid-19 pandemic. Data collection methods used are observation, documentation studies and interviews. For the data analysis method used is descriptive qualitative method. The results of the study show that the promotion strategy used by Hotel Duta Syariah to increase room sales during the Covid-19 pandemic is advertising, direct promotion and maximizing the use of sales promotion. The conclusion obtained is the result of the promotion strategy used in accordance with what was expected, there was an increase in room sales, especially during the post-covid period.